If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36M + 54 = 0 Reorder the terms: 54 + 36M = 0 Solving 54 + 36M = 0 Solving for variable 'M'. Move all terms containing M to the left, all other terms to the right. Add '-54' to each side of the equation. 54 + -54 + 36M = 0 + -54 Combine like terms: 54 + -54 = 0 0 + 36M = 0 + -54 36M = 0 + -54 Combine like terms: 0 + -54 = -54 36M = -54 Divide each side by '36'. M = -1.5 Simplifying M = -1.5
| 13z=65 | | 100x^2-60x+9=121 | | r-36=62 | | 16x^2-4x+9=81 | | 5m=40 | | 9p-4p+6=7p+6-3p | | 98-80=35y-44y | | r-2=4r+7 | | 2t-4t=10 | | x^2+9x+9=-5 | | 6+9n-5=9n+8-7n | | 6m=13m+28 | | 0=w^2+6w+150 | | 25x^2+40+16=28 | | 72=-9a | | b+6=4 | | 5x-(5+4x)=(3+x)-8 | | 8t+9t=102 | | 5x^2-17x=16 | | x^2+4x-17=-5 | | 45x-15y=20 | | 5x^2-17x-16=o | | 4a+3b+7a+3b= | | -3(4x-7)= | | 36=81x | | 27x-9y=30 | | 3x^3+4x^2-3x-23=0 | | V^2+v+2=4 | | 9x-3y=10 | | h-2=8 | | 2x^2-12+2x=x^2-4x+4 | | 6b-4a+a= |